Enhancing physicochemical and functional properties of jack bean (Canavalia ensiformis) starch with heat-moisture treatment - Beti Cahyaning Astuti; Choiroel Anam; M. Zukhrufuz Zaman; Danar Praseptiangga (Hasanuddin University Food Science and Technology Study Program, 2026)
Heat-moisture treatment (HMT) represents a standard procedure used to adjust the properties of jack bean starch (JBS) and enhance its functionality in food applications. Therefore, this study aimed to analyze the influence of HMT on the JBS’s functional and physicochemical properties. Native starch was subjected to HMT with varying moisture contents (15, 20, and 25%) and durations (1, 2, and 3 h) at a constant temperature of 110°C. The influence of HMT on the physicochemical properties, pasting properties, crystalline pattern, crystallinity, and morphology of starch granules was evaluated. Color analysis revealed a decline in lightness (L*) and greenness (a*), accompanied by an increase in yellowness (b*) as the heating time increased. Swelling power and solubility decreased with increasing moisture content. Meanwhile, amylose content increased with prolonged heating compared to that of native starch. Elevated moisture content and extended heating duration increased pasting temperature and peak time but simultaneously reduced breakdown viscosity. X-ray diffraction (XRD) exhibited that HMT maintained the A-type crystalline pattern of the native starch. Nevertheless, the crystallinity showed a complex trend, increasing at 25% moisture after one hour of heating (from 42.95 to 43.19%). FTIR spectra confirmed that HMT did not change the molecular structure of the starch, even though higher moisture content led to surface damage and granule cracking. HMT effectively modified jack bean starch, offering potential for improved functionality in food applications.